Body checking behaviors in anorexia nervosa. Issue 4 (24th January 2017) - Calugi, Simona; El Ghoch, Marwan; Dalle Grave, Riccardo
Abstract: The study aimed to assess the trajectories of change in body checking over time and the change in eating disorder and general psychopathology in patients with anorexia nervosa treated with inpatient enhanced cognitive behavioral therapy (CBT‐E). Sixty‐six adult patients with anorexia nervosa were recruited from consecutive referrals to a community‐based eating disorder clinic. Body mass index, Eating Disorder Examination, Brief Symptom Inventory, and Body Checking Questionnaire (BCQ) scores were recorded at admission (T0), end of treatment (T1), and 6‐ and 12‐month follow‐ups (T2 and T3, respectively). The BCQ was also administered at a single time point to an age‐matched healthy female comparison participants group ( N = 182). In comparison with comparison participants, patients had higher global BCQ scores at T0. However, mean patient scores for global BCQ administered at T1, T2, and T3 were significantly lower than that measured at baseline in the comparison participants group. The change in BCQ was significantly associated to short‐ and long‐term improvements in eating disorder and general psychopathology. The association between change in body checking and the trajectories of change of eating disorder psychopathology supports the potential usefulness of the CBT‐E strategy for reducing shape and weight concerns by addressing body checking.